Análise da terceirização nas instituições de ensino superior públicas no Estado de Goiás - (:unkn) unknown (Universidade Federal de Goiás, 2017)
The present work intends to verify the outsourcing in public higher education institutions of the State of Goiás, in order to trace a general theoretical reference, passing through the evolution of the productive systems and the insertion of outsourcing as a management tool, as well as legislation has addressed this phenomenon. In the study, it was divided into two parts, the first one a bibliometric study that aims to evaluate the scientific production on the subject of outsourcing tabulating the results obtained to understand the directions of scientific production on the subject. There has been a growing increase in production in recent years, but still with a lot of conceptual differences. The second study focused on the materialization of outsourcing in the public higher education institutions of the State of Goiás by means of the analysis of the outsourcing contracts and the judicial processes resulting from this contract, where it can be verified the constant increase of the use of this tool of Management in these organizations, but also the failures in contracts that lead to judicial convictions, demonstrating that there is in fact precarious work, since there are losses to workers in these conditions.
Analysis of outsourcing in public higher education institutions in the state of Goiás
Keywords: Terceirização; Administração pública; Contratos; Sentenças; Outsourcing; Public administration; Contracts; Sentences; CIENCIAS SOCIAIS APLICADAS